Diurnal Variation and Nursing Perspectives in Analgesic and Sedation Medication Administration to Mechanically Ventilated Children in a Single Pediatric ICU - Loberger, Jeremy M. (J Pediatr Intensive Care, 2021)
The primary objective of this study was to determine whether there was diurnal variation in the amount of analgesic and sedation medication administered to mechanically ventilated children in a single pediatric intensive care unit (PICU). The secondary objective was to evaluate nursing attitudes and practices regarding administration of these medications. This was a prospective, longitudinal cohort study of mechanically ventilated patients admitted to a single PICU. There were 46 mechanical ventilation courses included (305 paired day–night shifts). There was no significant diurnal variation found in the amount of analgesics and sedatives administered to mechanically ventilated patients. However, the reasons for administration differed between day and night shifts.